Repeated sprint training by elite cross-country skiers under hypoxic conditions does not influence their mucosal immune function to a greater extent than identical normoxic training - Born, D.-P.; Faiss, R.; Willis, S.; Strahler, J.; Holmberg, H. C.; Millet, G. P.; Sperlich, B. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Stress due to repeated exposure to hypoxia affects the mucosal immune system, as reflected in a reduced salivary concentration of immunoglobin-A (sIgA) (Tiollier et al. 2005). Moreover, adding a hypoxic stress to a very intensive form of training (i.e. repeated sprint training in hypoxia (RSH)) induced superior performance benefits compared to repeated sprint training in normoxia (RSN) (Faiss et al. 2013). With a positive correlation between decrease in sIgA and incidence of respiratory tract infection, we hypothesized that RSH may alter immune function and increase infection risk to a greater extent than RSN in elite cross-country skiers.